The Role of Innovative Leadership in Transforming Student Learning Effectiveness: A Review of Best Practices and Future Directions - Riddel, Mairian; Zulfikar, Idris Rahman (Development: Studies in Educational Management and Leadership, 2024)
The objectives of this research are to identify best practices of innovative leadership in educational settings and to suggest future directions for research and implementation in this field. A systematic review approach was employed to identify relevant literature from scholarly databases, academic journals, and reputable educational sources. The findings of the review indicate that innovative leadership is essential for enhancing the effectiveness of student learning. Innovative leaders are characterized by their visionary outlook, commitment to continuous improvement, and ability to cultivate a culture of innovation. By fostering collaboration, leveraging technology, and incorporating personalized learning strategies, innovative leaders create dynamic learning environments that enhance student engagement, motivation, and achievement. This review has significant implications for educational leaders, policymakers, and practitioners. By adopting innovative leadership practices, educational institutions can promote an innovative culture, support teacher professional development, and integrate effective instructional strategies.